Workplace Bullying as a Barrier to Gen Z Job Performance at Manufacturing Industry in Batam - Dhita Hafizha Asri; R. Nandini; Ratih Anggraini (Goodwood Publishing, 2026)
Purpose: This study examines the effect of ethical leadership on job performance among Generation Z employees in Batam’s manufacturing industry, while testing workplace bullying as a mediator and organizational concern as a moderator. Methodology: A quantitative survey design was employed. Data were collected through online questionnaires (Google Forms) administered to Generation Z employees in the manufacturing sector of Batam. Purposive sampling yielded 263 valid responses. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software. Results: Ethical leadership significantly and positively affected job performance and workplace bullying (reducing it). Workplace bullying does not exert a significant direct effect on job performance; however, it significantly mediates the relationship between ethical leadership and job performance. Organizational concern did not significantly moderate the relationship between ethical leadership and job performance. Conclusions: Ethical leadership enhances job performance and reduces workplace bullying among Generation Z employees. Although workplace bullying has no direct impact on job performance, it serves as a significant mediating pathway through which ethical leadership enhances employee performance. Organizational concern was not a significant moderator of this relationship. Limitations: The study is limited to Generation Z respondents in Batam’s manufacturing sector and relies on self-reported survey data, which may limit its external validity and generalizability. Contributions: The findings provide practical guidance for manufacturing firms to strengthen ethical leadership and reduce workplace bullying, thereby supporting improved performance among the Generation Z workforce.